FORMULATION AND EVALUATION OF MUCOADHESIVE BUCCAL PATCH BY USING GUAVA LEAVES EXTRACT - Kadam, Tejaswini Ananda; Kalasakar, Pallavi Kamble,Vaishnavi; Kalasakar, Vaishnavi; Kadam, Monika; Navghare, Vijay (International Journal of Pharma and Bio Sciences, 2025)
Nowadays, various products are available for the treatment of oral ulcers. However, they cannot remain in stable contact with the ulcer meanwhile, mucoadhesive patches remain stable on the ulcer and also provides a physical barrier to particles that come into contact with it. The aim of the research is to formulate a product that provides protective and healing properties to ulcer using guava leaves extract. Mucoadhesive drug delivery system has different advantage as compare to conventional dosage forms such as gels, capsules, tablets, lozenges, etc. Formulation of buccal patch helps to prevent first pass metabolism. This buccal patchhasdesirable properties like mechanical and physicochemical. Mucoadhesive buccal patch can evaluate by using different parameters such as stability testing, pH, folding endurance, diffusion study, swelling index, etc. Patch consist ofmucoadhesive characteristics due to use of significant ratio of polymer Carbopol 940 to HPMC K15.By using guava leaves different constituent like flavonoids (quercetin, rutin, Naringenin, catechin), Phenolic acids (gallic acid) and others are extracted through the extraction process.